Handbook of ecological restoration (Cambridge University Press, 2002)
This two-volume handbook is a comprehensive account of the rapidly emerging and vibrant science of the ecological restoration of habitats and species. Ecological restoration aims to achieve complete structural, functional, self-maintaining biological integrity following disturbance. In practice, any theoretical model is modified by a number of economic, social, and ecological constraints. Consequently, material that might be considered as rehabilitation, enhancement, re-construction, or re-creation is also included. Principles of Restoration defines the underlying principles of restoration ecology in relation to manipulations and management of the biological, geophysical, and chemical framework